MODEL PENGAJARAN ILMU TAUHID DI PONDOK PESANTREN AT-TAUHIDIYAH CIKURA BOJONG TEGAL DAN IMPLIKASINYA PADA PEMAHAMAN DAN SIKAP JAMAAHNYA - Supriyanto Supriyanto (IAIN Purwokerto, 2015)
Abstract: The results showed that the science of monotheism (ilmu Tauhid) became the main core of knowledge in Pondok Pesantren (PP) At-Tauhidiyah Cikura, Tegal. Teaching models developed are: (a) In the Pesantren At-Tauhidiyah, there are three kinds of approach that characterizes the exposure of monotheism, which is contained in the yellow books, namely: textual approach, Sufi approach, and a rational approach; (B) Effect of tharigah also very strongly influenced characteristics in the education process; (C) affiliated to the Tawheed wal Jama'ah ahlussunnah ala Ash'arite, particularly referring to the book by Imam Sanusi, namely Sanusiyah's theology; (D) The method developed in the teaching of monotheism in PPAt-Tauhidiyah is a method of textual harfiyah and semi rote; (E) sorogan and bandongan teaching model also remains a key used in PP At-Tauhidiyah. Keywords: Tauhid Science, Islamic boarding school